2019
DOI: 10.1186/s13023-019-1085-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adverse event profile from four completed trials of oral eliglustat in adults with Gaucher disease type 1

Abstract: Background Eliglustat is a first-line oral treatment for adults with Gaucher disease type 1 who have an extensive, intermediate or poor CYP2D6 metabolizer phenotype (> 90% of patients). Whereas enzyme replacement therapy for Gaucher disease has been widely used for more than two decades, eliglustat has only been in commercial use since 2014. Clinicians and patients want to better understand which adverse events are most commonly associated with eliglustat, as well as their severity, frequency, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
1
33
1
Order By: Relevance
“…The long‐term safety data from this trial extend the safety and tolerability profile of eliglustat reported among treatment‐naïve patients during 1.5 years in the Phase 3 ENGAGE trial, ERT switch patients during 4 years in the Phase 3 ENCORE trial, and mostly ERT switch patients in the EDGE trial comparing once‐ vs twice‐daily dosing of eliglustat . These 4 trials represent a total of 393 eliglustat‐treated patients and 1400.3 patient‐years of eliglustat exposure, with a mean duration of 3.6 years on eliglustat . Nineteen of the 20 patients who entered the Phase 2 trial extension after the 1‐year primary analysis completed the trial, with just one withdrawal at 2 years for administrative reasons.…”
Section: Discussionmentioning
confidence: 58%
“…The long‐term safety data from this trial extend the safety and tolerability profile of eliglustat reported among treatment‐naïve patients during 1.5 years in the Phase 3 ENGAGE trial, ERT switch patients during 4 years in the Phase 3 ENCORE trial, and mostly ERT switch patients in the EDGE trial comparing once‐ vs twice‐daily dosing of eliglustat . These 4 trials represent a total of 393 eliglustat‐treated patients and 1400.3 patient‐years of eliglustat exposure, with a mean duration of 3.6 years on eliglustat . Nineteen of the 20 patients who entered the Phase 2 trial extension after the 1‐year primary analysis completed the trial, with just one withdrawal at 2 years for administrative reasons.…”
Section: Discussionmentioning
confidence: 58%
“…Discontinuation could be attributable to adverse events, preference for ERT, limited commercial availability or reimbursement for eliglustat, or, in the seven women of childbearing age who discontinued treatment, because of pregnancy or desire to become pregnant, as eliglustat is not recommended for women during pregnancy. In a pooled analysis of adverse events from all four eliglustat clinical trials representing a mean of 3.6 years on treatment, 83% of patients remained in their trial until they were switched to commercial eliglustat (patients living in the United States) or the trial was completed, with 2.3% of the combined trial population discontinuing treatment due to an adverse event that was considered related to eliglustat 21 …”
Section: Discussionmentioning
confidence: 99%
“…The long-term outcome of treatment of patients suffering from GD with agents that reduce GSLs is, however, remarkably positive. No major side-effects are observed in individuals treated for a number of years (Mistry et al, 2018; Lewis and Gaemers, 2019). So far, the agents used do not achieve significant reduction in GSLs in the brain, however, a new generation of compounds aiming at that is being tested at the moment.…”
Section: Perspectivesmentioning
confidence: 99%